A gynaecologic perspective on cloacal malformations. Issue 5 (October 2015) - Cardamone, Stefanie; Creighton, Sarah
<x xml:space="preserve">Abstract</x> Purpose of review Advances in surgical reconstruction of cloacal malformations have led to better functional outcomes and quality of life. As a result, adolescents and women born with these complex malformations will have the same aspirations as their peers including sexual relationships and fertility. Recent findings Currently, there is a paucity of data on gynaecologic outcomes and sexual function, and obstetric data are limited primarily to case reports. Making evidence-based clinical recommendations is difficult for gynaecologic providers. Unique gynaecologic issues can arise in infancy, adolescence or adulthood. Recognition and appropriate management of these complications is imperative to maximize sexual esteem and preserve future fertility. Pregnancy requires adequate prenatal preparation and specialized multidisciplinary care under an experienced obstetrician and urologist. Summary This review highlights the issues that may be encountered in providing gynaecologic care to patients with cloacal malformations, presents the available literature to provide informative evidence and identifies gaps in knowledge in order to suggest potential future research opportunities.